Architecture and urbanism in the French Atlantic empire state, church, and society, 1604-1830 - Bailey, Gauvin Alexander 1966- (McGill-Queen's University Press, 2018)
"Spanning from the West African coast to the Canadian prairies and south to Louisiana, the Caribbean, and Guiana, France's Atlantic empire was one of the largest political entities in the Western Hemisphere. Yet despite France's status as a nation at the forefront of architecture and the structures and designs from this period that still remain, its colonial building program has never been considered on a hemispheric scale. Drawing from hundreds of plans, drawings, photographic field surveys, and extensive archival sources, Architecture and Urbanism in the French Atlantic Empire focuses on the French state's and the Catholic Church's ideals and motivations for their urban and architectural projects in the Americas. In vibrant detail, Gauvin Alexander Bailey recreates a world that has been largely destroyed by wars, natural disasters, and fires - from Cap-François (now Cap-Haïtien), which once boasted palaces in the styles of Louis XV and formal gardens patterned after Versailles, to failed utopian cities like Kourou in Guiana. Vividly illustrated with examples of grand buildings, churches, and gardens, as well as simple houses and cottages, this volume also brings to life the architects who built these structures, not only French military engineers and white civilian builders, but also the free people of colour and slaves who contributed so much to the tropical colonies. Taking readers on a historical tour through the striking landmarks of the French colonial landscape, Architecture and Urbanism in the French Atlantic Empire presents a sweeping panorama of an entire hemisphere of architecture and its legacy."
Keywords: Geschichte 1604-1830; Städtebau; Kolonie; Architektur; Frankreich; Atlantischer Raum; ARCHITECTURE / General; Architecture, French colonial; Architecture / Colonies / France; Architecture, French; France / Colonies / History; City planning / Colonies / France; Architecture and society / Colonies / France; French colonies; France; Architecture coloniale française; Architecture / France / Colonies; Architecture française; Urbanisme / France / Colonies; Architecture et société / France / Colonies; History